Identification of different respiratory viruses, after a cell culture step, by matrix assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) - Calderaro, Adriana; Arcangeletti, Maria Cristina; Rodighiero, Isabella; Buttrini, Mirko; Montecchini, Sara; Vasile Simone, Rosita; Medici, Maria Cristina; Chezzi, Carlo; De Conto, Flora (Scientific reports, 2016)
In this study matrix assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS), a reliable identification method for the diagnosis of bacterial and fungal infections, is presented as an innovative tool to investigate the protein profile of cell cultures infected by the most common viruses causing respiratory tract infections in humans. MALDI-TOF MS was applied to the identification of influenza A and B viruses, adenovirus C species, parainfluenza virus types 1, 2 and 3, respiratory syncytial virus, echovirus, cytomegalovirus and metapneumovirus. In this study MALDI-TOF MS was proposed as a model to be applied to the identification of cultivable respiratory viruses using cell culture as a viral proteins enrichment method to the proteome profiling of virus infected and uninfected cell cultures. The reference virus strains and 58 viruses identified from respiratory samples of subjects with respiratory diseases positive for one of the above mentioned viral agents by cell culture were used for the in vitro infection of suitable cell cultures. The isolated viral particles, concentrated by ultracentrifugation, were used for subsequent protein extraction and their spectra profiles were generated by MALDI-TOF MS analysis. The newly created library allowed us to discriminate between uninfected and respiratory virus infected cell cultures.